Demographic, Socio-economic, and Regional Fertility Differentials in Pakistan (The Pakistan Development Review, 1999)
Pakistan, with an estimated population of 135.6 million in 1999, is the seventh most populous country in the world. The historical trends indicate a continuous and exponentially increasing growth in population because of sustained high fertility and declining mortality. Currently, the population is growing at around 2.3 percent per annum, one of the highest rates of growth in the world. In Pakistan, the contraceptive prevalence is still low (24 percent) and fertility level (TFR 5.0) is among the highest in the world. There has been only a marginal decline in fertility in Pakistan over the last two and half decades. An average married woman in Pakistan still experiences a total of at least seven children if she survives and completes her reproductive periods. The purpose of this analysis using data from a nationally representative sample survey, Pakistan Fertility and Family Planning Survey 1996-97 [see Hakim et al. (1998) for details] is to determine whether there are any differentials in fertility levels by age at marriage, educational level, occupation, region of residence (province), place of residence (urban or rural) and economic class. Both bivariate and multivariate analyses have been undertaken to examine the effect of the selected demographic and socio-economic variables on the level of fertility. Some variations by use of contraception, exposure to mass media, mother tongue, women’s mobility and decision-making variables were also studied, but subsequently dropped because differentials were either not sustained or captured by other variables.